Does an increase in available nitrogen during the seed-filling period improve soybean seed physiological quality under field water deficit? - Ergo, Verónica Vanesa; Gallo, Carina Del Valle; Salvagiotti, Fernando; Carrera, Constanza Soledad (Sociedad Argentina de Fisiología Vegetal, 2024)
Poster